2011
DOI: 10.1002/bip.21688
|View full text |Cite
|
Sign up to set email alerts
|

Diverse role of conformational dynamics in carboxypeptidase A‐driven peptide and ester hydrolyses: Disclosing the “Perfect Induced Fit” and “Protein Local Unfolding” pathways by altering protein stability

Abstract: Catalytic mechanisms of carboxypeptidase A (CPA) are well known for their diversity and the relative inaccessibility for a decisive comprehension. Recent encouraging attempts through modern computational techniques promoted new challenges for the complementary experimental endeavors. In this work, we have applied the stopped-flow technique and the method of reaction progress curve fitting to extract kinetic parameters for the CPA-catalyzed hydrolyses of smaller (typical) peptide and ester substrates, known for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…15,16,20,21,[24][25][26][39][40][41][43][44][45][53][54][55]71 In the case of sluggish (viscous) environments, the slow modes of the protein's outer solution (e.g., of the water-doped [ch][dhp] melt), of the protein's peripheral (interfacial) zone, and even of the protein's metal core neighborhood may be essentially coupled, and form hierarchical (intrinsically subordinated) set of connections (see the following sections for further discussion). 15,16,20,21,[24][25][26][53][54][55][68][69][70][71][72][73] Accordingly, in the case of composite systems like ours, the classical Marcus relationship 43,45 for the outer-sphere component of the reorganization energy, l o(OS) p [A o À1 À A s À1 ] (where A o and A s are optical and static dielectric permittivity constants of the medium, respectively), is hardly applicable. 74,75 Anyway, the values of A o and A s , for choline-based PILs change little for respective binary mixtures above the [ch][dhp] mole fraction of ca.…”
Section: Paper Pccpmentioning
confidence: 99%
“…15,16,20,21,[24][25][26][39][40][41][43][44][45][53][54][55]71 In the case of sluggish (viscous) environments, the slow modes of the protein's outer solution (e.g., of the water-doped [ch][dhp] melt), of the protein's peripheral (interfacial) zone, and even of the protein's metal core neighborhood may be essentially coupled, and form hierarchical (intrinsically subordinated) set of connections (see the following sections for further discussion). 15,16,20,21,[24][25][26][53][54][55][68][69][70][71][72][73] Accordingly, in the case of composite systems like ours, the classical Marcus relationship 43,45 for the outer-sphere component of the reorganization energy, l o(OS) p [A o À1 À A s À1 ] (where A o and A s are optical and static dielectric permittivity constants of the medium, respectively), is hardly applicable. 74,75 Anyway, the values of A o and A s , for choline-based PILs change little for respective binary mixtures above the [ch][dhp] mole fraction of ca.…”
Section: Paper Pccpmentioning
confidence: 99%
“…It is well known that additives of urea cause proteins' thermodynamic destabilization [73,79], whereas TMAO, in general, efficiently stabilizes proteins [73,79]. In numerous publications, it has been demonstrated that the trends of proteins' stabilization/destabilization generally are accompanied with the decrease/increase of a fluctuational flexibility of proteins, such that the total unfolding (lack of secondary and tertiary structures) matches the maximal flexibility [73,[80][81][82].…”
Section: Kinetic Data On the Impact Of Temperaturementioning
confidence: 97%
“…It is well known that additives of urea cause proteins' thermodynamic destabilization [73,79], whereas TMAO, in general, efficiently stabilizes proteins [73,79]. In numerous publications, it has been demonstrated that the trends of proteins' stabilization/destabilization generally are accompanied with the decrease/increase of a fluctuational flexibility of proteins, such that the total unfolding (lack of secondary and tertiary structures) matches the maximal flexibility [73,[80][81][82]. Furthermore, it has been well established that Mb, in general, is a rather flexible protein that is required for the realization of its function − ligand binding/release through the "gating" motion of the protein matrix throughout the region of the "ligand channel" [32][33][34][44][45][46][47][48].…”
Section: Kinetic Data On the Impact Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…CPA was discovered in 1929 [18] and the first crystal of CPA was obtained from Bos taurus pancreas in 1937 [19]. It is a 35 kDa zinc-dependent metal carboxypeptidase, routinely obtained at an industrial scale from porcine or bovine pancreas [20]. It can cut off the C-terminal amino acid (especially aromatic amino acid) residues, but not proline, hydroxyproline, arginine, and lysine residues.…”
Section: Introductionmentioning
confidence: 99%